2022
DOI: 10.3389/fpsyg.2021.774173
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Competing Culture and Environmental Investment

Abstract: Using Chinese listed companies as research setting, this paper constructs a measure of corporate competing culture through textual analysis on firms’ management discussion and analysis (MD&A) disclosures, and examines the impact of corporate competing culture on environmental investment. The results show that competing culture has a significant and positive impact on firms’ environmental investment, and the results remain robust to a battery of robustness tests. Moreover, the mediating analysis indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…For example, the Wenchuan earthquake in 2008, the torrential rain in Beijing in 2012, the Typhoon Lichma in 2019 and the torrential rain in Henan in 2021 directly caused economic losses of 845.14 billion yuan, 11.64 billion yuan, 51.53 billion yuan and 114.269 billion yuan respectively. Moreover, as the largest carbon emitter globally, how to deal with the transformation risk is a major issue which is widely concerned by government, companies and the public (Tian et al, 2022a;Liu et al, 2022;Zhai et al, 2022). Therefore, this study is pioneering, which enriches research on precautionary cash holdings strategy adopted by Chinese listed companies to deal with climate risk.…”
Section: Introductionmentioning
confidence: 90%
“…For example, the Wenchuan earthquake in 2008, the torrential rain in Beijing in 2012, the Typhoon Lichma in 2019 and the torrential rain in Henan in 2021 directly caused economic losses of 845.14 billion yuan, 11.64 billion yuan, 51.53 billion yuan and 114.269 billion yuan respectively. Moreover, as the largest carbon emitter globally, how to deal with the transformation risk is a major issue which is widely concerned by government, companies and the public (Tian et al, 2022a;Liu et al, 2022;Zhai et al, 2022). Therefore, this study is pioneering, which enriches research on precautionary cash holdings strategy adopted by Chinese listed companies to deal with climate risk.…”
Section: Introductionmentioning
confidence: 90%
“…Previous research found that board independence (Liao et al, 2015;Post et al, 2015), board gender diversity (Glass et al, 2016;Atif et al, 2021), and Chief Executive Officer (CEO)'s experience and personality (Walls and Berrone, 2017;Arena et al, 2018) may affect the corporate carbon emissions reduction activities. Recent studies have also found that the board's Frontiers in Environmental Science frontiersin.org environmental orientation is helpful to increase environmentalrelated investment and effectively reduce carbon emissions (Dixon-Fowler et al, 2017;Moussa et al, 2020;Tian et al, 2021). In addition, shareholders and other stakeholders need to pay more attention to the disclosure of corporate carbon information (Matsumura et al, 2014).…”
Section: The Framework Of Enterprises Carbon Emissions Reductionmentioning
confidence: 99%
“…Second, firms that engage in green innovation can benefit from a reduced cost of compliance with government environmental regulations (Hart, 1995b). Third, green innovation can help firms improve their market position (Mirata and Emtairah, 2005;Bernauer et al, 2007;Tian et al, 2021). Fourth, green innovation can enhance firms' environmental reputation (Eiadat et al, 2008).…”
Section: Hypothesis Developmentmentioning
confidence: 99%